2019
DOI: 10.1002/etc.4413
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Selected Halogenated Organic Flame Retardants in Lake Ontario

Abstract: The trophic magnification of polybrominated diphenyl ethers (PBDEs) and selected nonlegacy halogenated organic compounds (HOCs) was determined in the food web of Lake Ontario (ON, Canada). In all, 28 Br3‐Br8‐PBDEs and 24 HOCs (10 of which had not been targeted previously) were analyzed. Average concentrations of Σ28PBDEs in fish ranged between 79.7 ± 54.2 ng/g lipid weight in alewife (Alosa pseudoharengus) and 815 ± 695 ng/g lipid weight in lake trout (Salvelinus namaycush). For invertebrates, concentrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…TMFs often vary strongly depending on the characteristics of the studied food web (e.g., biodiversity, food web dynamics, energy, and nutrient cycling), season and temperature of the studied ecosystem, the sampling strategies and coverage of taxa and species, and the system dynamics [9,[13][14][15][16][17][18][19][20]. For TL normalization, it would, therefore, be ideal to derive the TMFs directly in the ecosystem under consideration.…”
Section: The Last Column Lists the Protection Goals On Which The Eqs mentioning
confidence: 99%
See 2 more Smart Citations
“…TMFs often vary strongly depending on the characteristics of the studied food web (e.g., biodiversity, food web dynamics, energy, and nutrient cycling), season and temperature of the studied ecosystem, the sampling strategies and coverage of taxa and species, and the system dynamics [9,[13][14][15][16][17][18][19][20]. For TL normalization, it would, therefore, be ideal to derive the TMFs directly in the ecosystem under consideration.…”
Section: The Last Column Lists the Protection Goals On Which The Eqs mentioning
confidence: 99%
“…Among the studies compiled here, six report TL-corrected BMFs derived in addition to TMFs from parallel measurements of fish of different TL from one ecosystem (i.e., [15,20,33,40,41,43]; Table 2).…”
Section: Tl 4 Normalization Based On Trophic Level-corrected Bmf (Bmfmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, little data on bioaccumulation or biomagnification for PBT are available [8]. Kurt-Karakus et al [65] observed an enrichment in the freshwater food web of Lake Ontario but no trophic level-dependence of PBT accumulation.…”
Section: Flame Retardantsmentioning
confidence: 99%
“…TBP-DBPE was detected only in blue mussels from NS 2 and eelpout from BS in 2015. TBP-DBPE is assumed to be bioaccumulative [8,65]. Concentrations are in the same range as those reported by Sühring et al [61] for dabs from the German Bight.…”
Section: Flame Retardantsmentioning
confidence: 99%